HATE SPEECH UTTERED BY MOTHERS-IN-LAW TO DAUGHTERS-IN-LAW IN BALI: FORENSIC LINGUISTICS & PRAGMA-SEMANTIC APPROACH - I Gst. Ayu P. Jesika Sita Devi N, (Journal of Innovation Research and Knowledge, 2025)
Communication plays a vital role in expressing ideas and emotions, with verbal exchanges being key to conveying meaning. However, speech can sometimes be misused, resulting in harmful forms of expression like hate speech. Hate speech is considered a linguistic offense, often laden with malice and deeply offensive. This study examines the types of hate speech and the pragma-semantic analysis behind utterances made by mothers-in-law toward their daughters-in-law in Bali. Employing a descriptive qualitative approach, the research offers an in-depth data analysis. The study identifies seven utterances and four types of hate speech. The findings also show that locutionary, illocutionary, and perlocutionary acts are interconnected. Locutionary acts are articulated, illocutionary acts convey the intended meaning, and feedback is reflected in perlocutionary acts. For example, all hate speech expressed is baseless. This study contributes by highlighting how older individuals, particularly mothers-in-law, often use their mother language to express spontaneous hatred.